Left scrotal abscess associated with perforated appendicitis - Michaela Gaffley; Thomas Pranikoff; Avinash Shetty (Elsevier, 2020)
Acute appendicitis is a common disease afflicting the pediatric population. There are textbook presentations of periumbilical abdominal pain that migrates to the right lower quadrant with following nausea, possible diarrhea, anorexia, fever and eventual sepsis. The abnormal presentations are difficult to sort at times and varying presentations have been noted. The differential should remain broad in evaluating patients as our case illustrates. Keywords: Acute appendicitis, Amyand hernia, Scrotal abscess